(untitled) (Estudos em Design, 2022)
Quadro editorial Editores Cristina Portugal Rita Maria de Souza Couto Avaliadores desta edição v. 30, n. 1 (2022) Adriana Gralow Katia Miller Alexandre Santos Oliveira Aline Savi Álvaro José Barbosa Sousa Ana Beatriz Pereira de Andrade Ana Berwanger Ana Veronica Pazmino André Ribeiro de Oliveira Andréa de Souza Almeida Andréa Silva Antônio Ferreira Colchete Filho Beany Monteiro Carlo Franzato Carlos Delano Delano Rodrigues Cássia Letícia Carrara Chrystianne Goulart Ivanósk Clice Mazzilli Cristina Portugal Daniel Raposo Daniela Alves Danielle Silva Simões-Borgiani Deborah Chagas Christ Denise Portinari Doris Kosminsky Edson Rufino de Souza Eloiza Andrade Corrêa Eva Rolim Miranda Everton da Silva Fernando Fogliano Frederico Braida Filipe Campelo Xavier da Costa Gabriel Patrocínio Gabriela Carneiro Helena Neumann Isadora Dickie Joana Quental Joao Eduardo chagas Sobral Kando Fukushima Kátia CarvalhaesPêgo Laura Martins Leticia Affini Luiz Agner Luiza Novaes Luiza Falcão Soares Cunha Madalena Grimaldi Marcelo Bezerra Marcelos Forcato Márcio Guimarães Marcos Beccari Marcos Braga Maria Cristina Ibarra Mariano Lopes de Andrade Neto Marina Kunst Matheus Cezarotto Nelson Kuwahara Otniel Josafat López Altamirano Paula Piva Linke Paulo Cesar Ferrol Rafael Efrem Rafael Raposo Rafaella Peres Ranielder Fábio de Freitas Raimundo Diniz Raquel Noronha Ravi Passos Renata Wanderley Rosiane Pereira Alves Rogerio Jose Camara Rosimeri Franck Pichler Sandra Regina Rech Sandra Souza Sérgio Luciano da Silva Tiago Barros Pontes Silva Vera Damazio Virgínia Tiradentes Souto Viviane Nunes Wagner Bandeira Walter Correia Walter Neto